2019
DOI: 10.1186/s13104-019-4460-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary trends in the prevalence of anti-HDV antibodies among patients positive for HBsAg referred to a national laboratory in Cameroon from 2012 to 2017

Abstract: Objective The aim of this study was to update the data on the prevalence of anti-HDV antibodies in Cameroon. Results Antibodies against hepatitis Delta virus (Anti-HDV) were found in 16.48% (95% CI 11.46–18.77%) of 426 hepatitis B virus surface antigen positive patients in Cameroon. Remarkably, they were significantly higher among people over 40 years and those living in the East and South regions of Cameroon at 66.7%, 50%, and 40%, respectively. These results suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…A recent publication evaluating HBV and HDV epidemiology from Yakutia, Russia reported increasing HDV population in connection with a stable HBV prevalence [ 37 ]. Similar patterns of HDV incidence were also reported in Cameroon, Austria, and United States [ 38 41 ]. These reported shifts in HDV incidence mirror some of the structural breaks observed in our analyses.…”
Section: Discussionsupporting
confidence: 81%
“…A recent publication evaluating HBV and HDV epidemiology from Yakutia, Russia reported increasing HDV population in connection with a stable HBV prevalence [ 37 ]. Similar patterns of HDV incidence were also reported in Cameroon, Austria, and United States [ 38 41 ]. These reported shifts in HDV incidence mirror some of the structural breaks observed in our analyses.…”
Section: Discussionsupporting
confidence: 81%
“…HDV prevalence in HBV positive patients fluctuated from 2•15% in 2004 to 1•28% in 2010, then back up to 3•47% in 2014, before declining again to 0•89% in 2016 31 . Similar patterns of HDV incidence were also reported in Cameroon by Noubissi-Jouegouo, et al and in multiple datasets from the United States [32][33][34] . These reported shifts in HDV incidence mirror some of the structural breaks observed in our analyses.…”
Section: Secondary Cluster Analysis Further Identified Four Distinct Temporal Patterns Of Hdv/hbv Diagnoses Includingsupporting
confidence: 86%
“…In the only other study done in Cuba in 1988, an anti-HDV positivity of 8.3% was detected ( 11 ). While we cannot exclude false positive results in the previous study, the ELISA kit used in the present study is expected to reliably detect HDV antibodies with reported sensitivity and specificity values of above 98% ( 16 ). The difference may be related to the success of the Cuban hepatitis B prevention and control program, since HBV vaccination is the most influential factor concerning the prevalence of both diseases ( 17 ).…”
Section: Discussionmentioning
confidence: 65%